As contribuições dos afro-antilhanos para a formação fonético-linguística de Porto Velho - Soares, Sheila Maria Roque (2023)
The objective of this research is to examine in the historiography of Rondônia the period of construction of the Madeira Mamoré Railway with emphasis on the immigration of Afro-Antilleans and the permanence of their descendants in Porto Velho where they may have left their phonetic-linguistic marks, as they make use of the voiceless alveopalatal affricates [t¿] and voiced [d¿] so used in the phonetics of the capital of Rondônia and the difference in the use of rhotics in relation to the cities in the interior of Rondônia. To do this, we searched books, dissertations, theses, articles for everything that recorded the colonization process of Rondônia. Among the authors analyzed in the first chapter who bring historical marks are Ferreira (2005), Pinto (1993), Coelho (1982) and Silva (1984). The literature review is based on the researchers Blackman (2007, 2019 and 2020), Lima (2013), Sampaio (2010) and Schuindt (2014) dealing with Afro-Antilleans and the authors Cagliari (2002), Henriques (2007), Roberto (2016), Silva (2014) who deal with phonetics studies, Martinet (2014), Saussure (2012), with studies on linguistics and language. The importance of this research is to record for young people in basic education who are unaware of the history of the colonization of Rondônia and the process of linguistic formation so that this knowledge is not lost and the speeches of foreign pioneer descendants in the region are recorded through phonetic transcriptions. colonization of Porto Velho making them feel proud of their identity. To carry out the phonetic transcriptions, the methodology of descriptive phonetics was used, following the phonemic approach in which the sounds were analyzed acoustically with a special earphone, repeating the words to be transcribed several times using the International Phonetic Alphabet standards as an instrument. (IPA) which provides the global academic community with a notational standard for the phonetic representation of all languages. To understand the transcription rules, it was necessary to undergo phonetic training at the Instituto Linguístico de Porto Velho. We tried to avoid diacritics and secondary accents in order to simplify the transcription rules, using only the main accent of the words. For data analysis, we used videos recorded on YouTube of Afro-Antillean teachers who worked as literacy teachers at the beginning of the formation of schools in Porto Velho, extracting words containing the phonemes /t/, /d/ and /r/ from their speeches to their phonetic-linguistic analyses.